Re‐testing and misclassification of HIV‐2 and HIV‐1&2 dually reactive patients among the HIV‐2 cohort of The West African Database to evaluate AIDS collaboration. Issue 2 (12th August 2014) - Tchounga, Boris K; Inwoley, Andre; Coffie, Patrick A; Minta, Daouda; Messou, Eugene; Bado, Guillaume; Minga, Albert; Hawerlander, Denise; Kane, Coumba; Eholie, Serge P; Dabis, François; Ekouevi, Didier K; et al.
Abstract : Introduction: West Africa is characterized by the circulation of HIV‐1 and HIV‐2. The laboratory diagnosis of these two infections as well as the choice of a first‐line antiretroviral therapy (ART) is challenging, considering the limited access to second‐line regimens. This study aimed at confirming the classification of HIV‐2 and HIV‐1&2 dually reactive patients followed up in the HIV‐2 cohort of the West African Database to evaluate AIDS collaboration. Method: A cross‐sectional survey was conducted from March to December 2012 in Burkina Faso, Côte d'Ivoire and Mali among patients classified as HIV‐2 or HIV‐1&2 dually reactive according to the national HIV testing algorithms. A 5‐ml blood sample was collected from each patient and tested in a single reference laboratory in Côte d'Ivoire (CeDReS, Abidjan) with two immuno‐enzymatic tests: ImmunoCombII ® (HIV‐1&2 ImmunoComb BiSpot – Alere) and an in‐house ELISA test, approved by the French National AIDS and hepatitis Research Agency (ANRS). Results: A total of 547 patients were included; 57% of them were initially classified as HIV‐2 and 43% as HIV‐1&2 dually reactive. Half of the patients had CD4≥500 cells/mm 3 and 68.6% were on ART. Of the 312 patients initially classified as HIV‐2, 267 (85.7%) were confirmed as HIV‐2 with ImmunoCombII ® and in‐house ELISA while 16 (5.1%) and 9 (2.9%) were reclassified as HIV‐1 and HIV‐1&2, respectively (Kappa=0.69; p <0.001). Among the 235 patients initially classified as HIV‐1&2 dually reactive, only 54 (23.0%) were confirmed as dually reactive with ImmunoCombII ® and in‐house ELISA, while 103 (43.8%) and 33 (14.0%) were reclassified as HIV‐1 and HIV‐2 mono‐infected, respectively (kappa= 0.70; p <0.001). Overall, 300 samples (54.8%) were concordantly classified as HIV‐2, 63 (11.5%) as HIV‐1&2 dually reactive and 119 (21.8%) as HIV‐1 (kappa=0.79; p <0.001). The two tests gave discordant results for 65 samples (11.9%). Conclusions: Patients with HIV‐2 mono‐infection are correctly discriminated by the national algorithms used in West African countries. HIV‐1&2 dually reactive patients should be systematically investigated, with a standardized algorithm using more accurate tests, before initiating ART as at least 4 out of 10 of them could initiate an effective first‐line ART for HIV‐1 and optimize their second‐line treatment options.